Study on zingiber puberulum oil using supercritical fluid extraction (SFE) - Omar, Muhammad Nor; Razman, Summaiya; Zuberdi, Ahmad Muzammil (2013)
Supercritical fluid extraction (SFE) technique was employed to extract the essential oil from the inflorescence of Zingiber puberulum at 48 Mpa and 40°C of extracting pressure and temperature respectively. The oil was then analysed using gas chromatography-mass spectrometry (GC-MS) instrument. Twenty-one compounds were found in the SFE extract of Z. puberulum with palmitic acid (65.7%), 1-heptatriacotanol (16.9%) and oleic acid (15.9%) were the major constituents. Small percentages of various terpenic compounds, i.e. α-bisabolol, β-elemene and caryophyllene were also identified. It was found that SFE could be used successfully to extract a wide variety of important bioactive compounds in Z. puberulum but that the conditions may need to be optimized to ensure the optimum yield of the volatile compounds.